The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ygcen.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a tachykinin signalling system in the bivalve mollusc Crassostrea gigas

Abstract: Although tachykinin-like neuropeptides have been identified in molluscs more than two decades ago, knowledge on their function and signalling has so far remained largely elusive. We developed a cell-based assay to address the functionality of the tachykinin G-protein coupled receptor (Cragi-TKR) in the oyster Crassostrea gigas. The oyster tachykinin neuropeptides that are derived from the tachykinin precursor gene Cragi-TK activate the Cragi-TKR in nanomolar concentrations. Receptor activation is sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 59 publications
3
21
1
Order By: Relevance
“…The relatively high expression of oyster signalling components in the mantle edges (Dubos et al, 2003), a tissue involved in shell biomineralization (Geraerts, 1976), is strongly suggestive of such a role. In contrast to some oyster signalling systems (Bigot et al, 2012;Dubos et al, 2018;Schwartz et al, 2018), we found no involvement of the oyster CT signalling system in feeding regulation. This diverges from the role of DH31 in feeding regulation in arthropods (Nagata and Nagasawa, 2017).…”
Section: Biological Implications Of the Oyster Ct Signalling Systemscontrasting
confidence: 99%
See 1 more Smart Citation
“…The relatively high expression of oyster signalling components in the mantle edges (Dubos et al, 2003), a tissue involved in shell biomineralization (Geraerts, 1976), is strongly suggestive of such a role. In contrast to some oyster signalling systems (Bigot et al, 2012;Dubos et al, 2018;Schwartz et al, 2018), we found no involvement of the oyster CT signalling system in feeding regulation. This diverges from the role of DH31 in feeding regulation in arthropods (Nagata and Nagasawa, 2017).…”
Section: Biological Implications Of the Oyster Ct Signalling Systemscontrasting
confidence: 99%
“…Lophotrochozoa, including annelids (Bauknecht and Jékely, 2015) and molluscs (Veenstra, 2010;Adamson et al, 2015;Zatylny-Gaudin et al, 2016;Ahn et al, 2017;Zhang et al, 2018) such as the oyster Crassostrea gigas (Stewart et al, 2014). In this species, large-scale genomic and transcriptomic resources (Zhang et al, 2012;Riviere et al, 2015) are now available, and facilitate the study of signalling pathways (Bigot et al, 2014;Dubos et al, 2018;Li et al, 2016;Schwartz et al, 2018). The present study investigated the evolution of the calcitonin (CT)/diuretic hormone 31 (DH31) signalling system in the bivalve mollusc C. gigas.…”
Section: Introductionmentioning
confidence: 99%
“…The complement system is considered to be an important element of the innate immune system that also triggers the adaptive immunity in higher animals in the animal kingdom. Similar hemolytic complement-like activity was also reported against parasites and other pathogens in molluscs [20,21].…”
Section: Complement Systemsupporting
confidence: 81%
“…Accordingly, new signalling systems have recently been discovered in the annelid Platynereis dumerilii 12 , 13 and in the mollusc Crassostrea. gigas 14 16 . The present study investigates the evolution of the gastrin/cholecystokinin (G/CCK)/sulfakinin (SK) signalling system in Lophotrochozoa, using the mollusc C. gigas as a representative species.…”
Section: Introductionmentioning
confidence: 99%